2013
DOI: 10.1159/000348395
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Improves Subclinical Temporal Dispersion of Distal Compound Muscle Action Potential in Anti-MAG/SGPG Neuropathy Associated with Waldenström Macroglobulinemia: A Case Report

Abstract: Patients with anti-myelin-associated glycoprotein (MAG)/sulfated glucuronyl paragloboside (SGPG) neuropathy associated with Waldenström macroglobulinemia show demyelinating neuropathy, but the temporal dispersion of distal compound muscle action potential (CMAP) in motor nerve conduction studies (NCS), which represents heterogeneous demyelination at the motor nerve terminal, is rare. We report on a 70-year-old man with anti-MAG/SGPG neuropathy associated with Waldenström macroglobulinemia; he had a 2-year hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Similar to Bing–Neel syndrome, anti-MAG neuropathy may be treated with rituximab and/or bendamustine. When treated with rituximab monotherapy in a multicenter study, 44% of patients with anti-MAG secondary to WM saw overall improvement, with one case reporting significant improvement in compound muscle action potential in nerve conduction studies [ 34 , 35 ]. In one case diagnosed with both anti-MAG neuropathy and Bing–Neel syndrome, bendamustine monotherapy resolved sensory disturbance and weakness, improvement in nerve conduction studies, and normalized serum IgM levels [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Bing–Neel syndrome, anti-MAG neuropathy may be treated with rituximab and/or bendamustine. When treated with rituximab monotherapy in a multicenter study, 44% of patients with anti-MAG secondary to WM saw overall improvement, with one case reporting significant improvement in compound muscle action potential in nerve conduction studies [ 34 , 35 ]. In one case diagnosed with both anti-MAG neuropathy and Bing–Neel syndrome, bendamustine monotherapy resolved sensory disturbance and weakness, improvement in nerve conduction studies, and normalized serum IgM levels [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…5558 These studies suggested a limited beneficial effect in some patients. Case reports have shown decreased IgM levels in IgM monoclonal gammopathy associated neuropathy and improvement of neuropathy in cases of anti-myelin-associated glycoprotein (MAG)/sulfated glucoronyl paragloboside (SGPG) associated Waldenström macroglobulinemia with rituximab treatment 56,58 . There have also been case reports of a neuropathy flare in WM following rituximab therapy.…”
Section: Treatmentmentioning
confidence: 99%